Tata Kelola Manajemen Sumber Daya Manusia dalam Dunia Pendidikan - Miswan Gumanti; Leni Anggraeni; Nurlela Nurlela; Sariyah Astuti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Each operation in a business, includes schools and colleges, depends extensively on the resources of human resources (HR). To make it possible for employees to contribute to the tasks and duties they perform at the company that they're responsible for, employees must be efficiently handled by the people who handle them. The objective of this study is to better understand and assess the application of human resources management (HRM) guidelines and procedures within the context of educational institutions. In an effort to recognize distinct methods and strategies in human resource management in colleges and universities, the investigation employs the approach commonly used in libraries, particularly includes gathering and assessing appropriate material. Both primary and secondary sources are the two types of sources of information. The results underscore how important the administration of human resources is to the process of learning as an entire. subsequently Also it will be expected that the imperfections and difficulties affecting the Indonesian nation, especially those associated with global competitiveness, could be resolved with efficient recruitment and hiring techniques.